3D-print infill generation using the biological phase field of an optimized discrete material orientation vector field. (1st March 2022) - Ichihara, Naruki; Ueda, Masahito
Abstract: A framework to produce an optimized infill structure for 3D-printed curvilinear fiber-reinforced polymer composites is proposed. The material orientation was optimized first to maximize the physical properties. Then, the phase field of the stripe pattern was developed based on the optimized material orientation vector field using the local activation and long-range inhibition system for the formation of biological patterns. Finally, the phase field was converted into a 3D print path. The proposed approach was validated both numerically and experimentally. The optimized infill structure showed a higher structural stiffness compared with commonly used infill structures prepared via concentric or rectilinear strategies, demonstrating the advantage of the proposed method.